Galactocele - Ferreira, Ciro; Harretche, Martín (Cirugía del Uruguay, 1984)
We have found a clinical case corresponding to a galactocele, knowing this is a rare occurrence. The pre• sumptive diagnosis may be established through !he cli• nical characteristics and the lactation background; but the confirmed diagnosis is made by mammography. The treatmeht mus! be surgical extirpation.